2013
DOI: 10.1590/0103-6440201301904
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Silorane and Methacrylate-Based Composites on the Polymerization Heat Generated with Different Light-Curing Units and Dentin Thicknesses

Abstract: This study evaluated the temperature variation in the pulp chamber during photoactivation of two restorative composite resins (Filtek P90 silorane-based composite and Heliomolar methacrylate-based composite) with either a quartz-tungsten-halogen (QTH) or light-emitting diodes (LED) light-curing unit (LCU) and using dentin thicknesses (0.5 and 1.0 mm). Standardized cavities (2x2x2 mm) were prepared in 80 bovine incisors, which were randomly assigned to 8 groups according to the photoactivation method and dentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…The second part of the current study investigated the effect of dentin thickness on the recorded temperature rise. Studies have suggested that dentin thickness is a critical factor that influences the amount of temperature rise in the pulp chamber because of the low thermal conductibility of this normal structure [42,43]. The present study confirmed this because differences were observed in the temperature rise between dentin thicknesses.…”
Section: Discussionsupporting
confidence: 87%
“…The second part of the current study investigated the effect of dentin thickness on the recorded temperature rise. Studies have suggested that dentin thickness is a critical factor that influences the amount of temperature rise in the pulp chamber because of the low thermal conductibility of this normal structure [42,43]. The present study confirmed this because differences were observed in the temperature rise between dentin thicknesses.…”
Section: Discussionsupporting
confidence: 87%
“…The second part of the study investigated the effect of increasing dentin thickness on the recorded temperature rise. According to Guiraldo et al [39], dentin thickness is a critical factor that in uences the amount of heat reaching the pulp, due to the low thermal conductibility of dentin [35]. The present study con rmed this because differences were observed in the temperature rise among dentin thicknesses.…”
Section: Discussionsupporting
confidence: 81%
“…The second part of the current study investigated the effect of dentin thickness on the recorded temperature rise. Studies have suggested that dentin thickness is a critical factor that in uences the amount of temperature rise in the pulp chamber 42 because of the low thermal conductibility of this normal structure. 43 The present study con rmed this because differences were observed in the temperature rise between dentin thicknesses.…”
Section: Discussionmentioning
confidence: 99%